ANALISIS KELAYAKAN FINANSIAL USAHA TERNAK AYAM RAS PETELUR (STUDI KASUS TAKIHARA FARM) DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Yuni Arda Br Saragih; Bustanul Arifin; Dyah Aring Hepiana Lestari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The aims of this research are to analyze the financial feasibility and the sensitivity of laying hens farming.  The research was a case study at Takihara Farm in Natar Subdistrict of South Lampung Regency.  Data were collected in August 2020 and analyzed by using financial feasibility and sensitivity analysis methods.  The results showed that laying hens farming was financially profitable and feasible to be developed.  The NPV of laying hens farming was IDR10,131,628,683.22.  The Gross B/C value of laying hens farming was 1.15.  The Net B/C value of laying hens farming was 2.17.  The Payback Period value of laying hens farming was 13.81 years, showing that the initial cash outflow of investment could be recovered less than 30 years.  The IRR value of laying hens farming was 13.84 percent, which was greater than interest rate 6 percent.  Based on the results of the sensitivity analysis, with an assumption of an increase in the production costs of corn as a feed ingredient for laying hens by 10.73 percent and a decrease in the selling price of chicken eggs by 12.44 percent, the business of laying hens farming is still worth cultivated and developed.Key words : financial, laying hens, sensitivity